Przyczynek do tematu: przekład w systemie literatury. Przy okazji słoweńskiej wersji Dziennika Witolda Gombrowicza / A Contribution to the topic: a translation in the system of culture. About the Slovenian translation of Witold Gombrowicz’s Dziennik (Diar - Kopczyk, Michał (Przekłady Literatur Słowiańskich, 2009)
The subject of the analysis made in the article is the translation of Witold Gombrowicz’s Diary (1904—1969) into the Slovenian language. This translation has a specific character, because the translator has shortened the original text — he decides what fragment of the work will reach the reader. The author of the article assumes that Slovenian literary consciousness is shown in the translator’s decision. With this in mind the Diary is treated mainly as a testimony of time, and less often as a literary piece, therefore intervention such as shortening is admissible. Then the author shows examples in which shortening the text changed its meaning. In the conclusions the author acknowledges that in the case of interpreting the translation, one can view the translator as a co-author of the work. As a result of his decision the work strays in many places from the shape of the original — however it also creates separate senses. The translator’s solutions were determined by different location of this literary kind in the sphere of the Polish culture and the culture receiving the work (Slovenian).